2020
DOI: 10.1111/ppc.12703
|View full text |Cite
|
Sign up to set email alerts
|

The examination of the relationship between nursing students' depression, anxiety and stress levels and restrictive, emotional, and external eating behaviors in COVID‐19 social isolation process

Abstract: Purpose This study was conducted to examine the relationship between students' anxiety, depression, stress levels, and emotional, external, restrictive eating behaviors in the coronavirus disease 2019 (COVID‐19) process. Design and Methods This study was conducted in included university involving 411 nursing students who completed the Personal Information Form, Depression, Anxiety, Stress Scale, and the Dutch Eating Behavior Questionnaire. Kruskal–Wallis Test, Mann–Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 51 publications
5
41
1
3
Order By: Relevance
“…All these variables have been previously discussed, with the exception of the size of the residences. This variable is a predictive variable of the NAS in T&R. Although currently, no studies are foreseen for this group, the study by Kalkan Ugurlu et al ( 2021 ) indicated that in the case of students, the size of the residence had no relevance on the emotional state, as was also the case for our sample of students.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…All these variables have been previously discussed, with the exception of the size of the residences. This variable is a predictive variable of the NAS in T&R. Although currently, no studies are foreseen for this group, the study by Kalkan Ugurlu et al ( 2021 ) indicated that in the case of students, the size of the residence had no relevance on the emotional state, as was also the case for our sample of students.…”
Section: Discussionsupporting
confidence: 47%
“…The impact upon basic processes such as eating and sleeping habits is present in all groups, but differs by sex, as the impacts are more intense among women, as pointed out in previous studies on university students (Kalkan Ugurlu et al, 2021 ) or specifically in the case of female students when examining body dissatisfaction (Nolan et al, 2010 ). The negative effects of sleeping habits on emotional states are related to its fundamental role in recovering energy (Scotta et al, 2020 ); correspondingly, altered sleeping habits are related to changes in lifestyle, unstable economic resources, and social distance (Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…The study of Kalkan Uğurlu et al, who worked on 411 Turkish hospital staff members, showed high quality based on NOS and reported the anxiety prevalence of about 33%. 46 Huang et al, who worked on 2250 Chinese health workers, reported the prevalence of 35% among participants. 47 However, in the study of Luceño-Moreno et al on 1422 health workers in Spain, the prevalence of anxiety was reported to be 20%, while we determined it as a medium-quality study.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura aponta que durante a pandemia o comer emocional se tornou comum entre estudantes, que passaram a buscar alimentos específicos ou elevar o número de refeições em função das emoções (Serin & Koç, 2020). A relação entre as emoções e o consumo alimentar durante o período de distanciamento social pode levar ao desencadeamento de episódios de compulsão, sendo ainda mais intenso entre indivíduos do sexo feminino e com excesso de peso prévio (Flaudias et al, 2020;Kalkan Uğurlu, Mataracı Değirmenci, Durgun, & Gök Uğur, 2021).…”
Section: Discussionunclassified